Use of photo biomodulation as complementary therapy in the treatment of feline sporotrichosis: A case report (Research, Society and Development, 2024)
Sporotrichosis is a zoonosis caused by fungi from the Sporothrix complex, which affects endothermic animals, with cats being the most affected animal. Transmission can occur via the classic route or, the alternative, the second being when an animal with the disease infects another animal or person. The treatment of choice for feline sporotrichosis is itraconazole, consisting of a long treatment and refractory cases have already been reported. Photo biomodulation is an alternative treatment that aims to assist conventional treatment, and its main advantages are analgesia, modulation of inflammation, acceleration of tissue repair, and an easy-to-apply technique. This article aims to report a clinical case of feline sporotrichosis refractory to treatment with itraconazole, in which it was decided to combine laser therapy as support for conventional treatment. The disease diagnosis was defined based on the cytopathological examination of the skin lesions and the treatment carried out with the oral antifungal itraconazole associated with weekly laser therapy sessions, resulting in complete remission of clinical signs. This study reinforces the importance of investigating and implementing alternative therapies for feline sporotrichosis, highlighting photo biomodulation as an excellent complementary option for this disease.